Farm financing in PNDR 2007-2013 - Mihnea-Iulian Vasiliu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
In Romania we are at the conclusion of the second agricultural financing program since the country's adherence to the European Union and in the transition period towards the next financial exercise. The experience and effects of the first program, that took place between 2007 and 2013, led to a new approach. The results of the 2014-2020 program will be concluded in an ex-post analysis. The family farms have been supported through dedicated measures, in both the first and in the second program, but in what follows I will detail the experience of the 2007-2013 financial exercise in regards to the 1st Axis, with an emphasis on measure 121, named "modernising agricultural exploitations - the family farm". The materials and sources used for this analysis are part of the specialty literature. This study has at its basis Romanian and European Union specialty literature and legislation, such as: regulations, decisions, directives, The National Rural Development Program, guides related to the aforementioned measure. The data collecting, processing, analysis, interpreting and synthesizing of said data have been used as a work method. Quantifying the impact of european funds for agriculture on family farms can be achieved through the dedicated measures from the analysed period and at the end of the currently ongoing agricultural census we will have a clearer bigger picture of the status of these farms in Romania.
Keywords: R51; Q14; 330; financing; PNDR; guide; farm; absorption